Atypical Presentation: Metastatic Uveal Melanoma in a Young Patient without Visual Complaints - Buiar, Pedro Grachinski; Azevedo, Sérgio Jobim de (Frontiers in Oncology, 2017)
Background Uveal melanoma is a rare and aggressive subtype of melanoma, with singular characteristics that separate it from the most famous cutaneous melanoma. This uncommon condition becomes even rarer if we look at young population. Common chemotherapy regimens does not work with this aggressive disease in its metastatic scenario, and the new armament like targeted and immunotherapies are still looking for more robust evidence. Case presentation We report a rare case of uveal melanoma in a patient younger than 20 years, with abdominal pain as his initial complaint. He did not present the typical visual symptoms of the primary site because of an auto accident suffered 4 months before the presentation, letting him blind of the eye affected by the tumor development. Conclusion There is always a possibility of the diagnosis of uveal melanoma in cases with associated isolated hepatic metastases, even in a young population, where this hypothesis is often rejected by the epidemiological frequency of other tumors. This rare case is a useful example.